If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + 5x = x Solving 60 + 5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 60 + 5x + -1x = x + -1x Combine like terms: 5x + -1x = 4x 60 + 4x = x + -1x Combine like terms: x + -1x = 0 60 + 4x = 0 Add '-60' to each side of the equation. 60 + -60 + 4x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 4x = 0 + -60 4x = 0 + -60 Combine like terms: 0 + -60 = -60 4x = -60 Divide each side by '4'. x = -15 Simplifying x = -15
| x+237=895 | | 2x-(3x-6)=5 | | 2f(x)=7x-5 | | 8x=6x+2x | | 4x+7=.5(8x+12)+1 | | 3/20p=5 | | 0.4x-0.3x+0.4x=2 | | 144+16x=x | | 1/3j=9j | | -5(v+2)+2v+6=6v+10 | | 2v=6v-8 | | -9w=-8-8w | | b-4.7=3.5 | | ∞/∞ | | 11x+-6y=3 | | ln(8)-5ln(2)=ln(x) | | Y=-9x^2-18x-1 | | 5-5x-10=9+2x-7 | | 3q-10=10-7q | | B/3-7=-7 | | (-7,9);m=4/5 | | 5(x+7)=3(x-(8-x)) | | -5m-9+m=-5 | | 550+12=22 | | -7+4(n-1)=-5(-n+5)-8n | | 550+22=12 | | 2/3-x/4=1/13 | | 12(3x-1)=9(3x+1)+24 | | 5/6x-15=10 | | -ln(1/3)=ln(x) | | 16/25-u/5 | | (10x^2+4)=-35 |